SDHB and SDHD silenced pheochromocytoma spheroids respond differently to tumour microenvironment and their aggressiveness is inhibited by impairing stroma metabolism. (1st May 2022) - Martinelli, Serena; Riverso, Maria; Mello, Tommaso; Amore, Francesca; Parri, Matteo; Simeone, Irene; Mannelli, Massimo; Maggi, Mario; Rapizzi, Elena
Abstract: Germline mutations in more than 20 genes, including those encoding for the succinate dehydrogenase (SDH), predispose to rare tumours, such as pheochromocytoma/paraganglioma (PPGL). Despite encoding for the same enzymatic complex, SDHC and SDHD mutated PHEO/PGLs are generally benign, while up to 80% of SDHB mutated ones are malignant. In this study, we evaluated the different effects of tumour microenvironment on tumour cell migration/invasion, by co-culturing SDHB or SDHD silenced tumour spheroids with primary cancer-associated fibroblasts (CAFs). We observed that SDHD silenced spheroids had an intermediate migration pattern, compared to the highest migration capability of SDHB and the lowest one of the wild type (Wt) spheroids. Interestingly, we noticed that co-culturing Wt, SDHB and SDHD silenced spheroids with CAFs in low glucose (1 g/l) medium, caused a decreased migration of all the spheroids, but only for SDHB silenced ones this reduction was significant. Moreover, the collective migration, observed in high glucose (4.5 g/l) and characteristic of the SDHB silenced cells, was completely lost in low glucose. Importantly, migration could not be recovered even adding glucose (3.5 g/l) to low glucose conditioned medium. When we investigated cell metabolism, we found that low glucose concentration led to a reduction of oxygen consumption rate (OCR), basal and maximal oxidative metabolism, and ATP production only in CAFs, but not in tumour cells. These results suggest that CAFs metabolism impairment was responsible for the decreased invasion process of tumour cells, most likely preventing the release of the pro-migratory factors produced by CAFs. In conclusion, the interplay between CAFs and tumour cells is distinctive depending on the gene involved, and highlights the possibility to inhibit CAF-induced migration by impairing CAFs metabolism, indicating new potential therapeutic scenarios for medical therapy. Highlights: SDHB and SDHD silenced spheroids respond differently to tumour microenvironment. Tumour aggressiveness is inhibited by impairing stroma metabolism. Glucose concentration modulates ATP only in stroma cells, but not in tumours.